2019
DOI: 10.1108/bfj-02-2019-0128
|View full text |Cite
|
Sign up to set email alerts
|

Gender and wine consumption: sociodemographic profiles

Abstract: Purpose The globalization of wine markets together with a prolonged decline in wine consumption, especially in traditional wine-producing countries such as Spain, make it more relevant than ever to study population segments such as female wine consumers. Such segments could contribute to increasing consumption. The purpose of this paper is to investigate the distinctive features of wine consumption according to gender, identifying sociodemographic profiles of female wine consumers and non-consumers in Tenerife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…This conclusion may not be consistent across ages as it was reported that Italian neophobic Millennials were those who less frequently consumed wine (Castellini and Samoggia, 2018). Another study conducted in Spain by Rodríguez-Donate et al (2017) found that women drank less wine than men, but it also showed that the segment of women wine consumers was highly heterogeneous (Rodríguez-Donate et al, 2019). Thus, the differences in findings between neophobic and neophilic female consumers may clearly be accounted for by the marked heterogeneity of women.…”
Section: Determination Of Wine Neophobia In Men and Women And Their S...mentioning
confidence: 89%
“…This conclusion may not be consistent across ages as it was reported that Italian neophobic Millennials were those who less frequently consumed wine (Castellini and Samoggia, 2018). Another study conducted in Spain by Rodríguez-Donate et al (2017) found that women drank less wine than men, but it also showed that the segment of women wine consumers was highly heterogeneous (Rodríguez-Donate et al, 2019). Thus, the differences in findings between neophobic and neophilic female consumers may clearly be accounted for by the marked heterogeneity of women.…”
Section: Determination Of Wine Neophobia In Men and Women And Their S...mentioning
confidence: 89%
“…Adinolfi et al [37] suggested that there are consumers who are "sensible" to the meaning and importance of designations of origin and others who are "indifferent". Socio-demographic factors also play a role in the perception of PDO wines [45][46][47]. According to Capitello et al [48], consumer attitudes, preferences, wine knowledge, and experience play an even higher role in PDO wine perception than socio-demographic characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, older consumers tend to drink more frequently, while consumers aged 25-34 are more likely to drink larger amounts. This same age group (i.e., [25][26][27][28][29][30][31][32][33][34] is recognized as the group with the highest percentage (29%) of wine drinkers in Poland, followed by the 35-44 age group (28%) (Statista, 2022). Recent research on wine consuming preferences conducted in Croatia (Alpeza et al, 2023) showed that consumption frequency commonly increases with age.…”
Section: Literature Reviewmentioning
confidence: 99%